Transformasi Manajemen Kinerja: Kontribusi Perencanaan, Pelatihan, dan Penilaian Terhadap Efektivitas Manajemen Kinerja Pegawai - Meilinda, Dhevi; Sutianingsih, Sutianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is quantitative research used to see the influence of planning, training and assessment on the effectiveness of performance management. This research sample used 30 respondents, with a saturated sampling technique. The factor variables of this research are planning, training and planning, the affected variable is the effectiveness of performance management. The results of this research found that planning had an influence on performance management of 0.190%, training had an influence on the effectiveness of performance management of 0.457%, assessment had an influence on the effectiveness of performance management of 0.379%. And based on the results of the F test, it shows that the regression model used is appropriate because the research data produces a significant value below 0.05. The results of the coefficient of determination also show a value of 53.6%. It can be said that performance planning, performance training and performance appraisal have an influence of 53.6% and the other 46.4% is influenced by other factors. Keywords: planning, training, assessment, performance